2004
DOI: 10.1007/s10038-004-0182-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the cardiac sodium channel gene SCN5A in Koreans with Brugada syndrome

Abstract: The SCN5A gene encodes the alpha subunit of the human cardiac voltage-gated sodium channel. Mutations in SCN5A are responsible for Brugada syndrome, an inherited cardiac disease that leads to idiopathic ventricular fibrillation (IVF) and sudden death. In this study, we screened nine individuals from a single family and 12 sporadic patients who were clinically diagnosed with Brugada syndrome. Using PCR-SSCP, DHPLC, and DNA sequencing analysis, we identified a novel single missense mutation associated with Bruga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(27 reference statements)
1
8
0
1
Order By: Relevance
“…Several recent studies have described BS patients with no SCN5A mutations (Smits et al, 2002;Takahata et al, 2003;Shin et al, 2004). These results are consistent with our findings, which provide support for the possibility of genetic heterogeneity in BS (Priori et al, 2000).…”
Section: Discussionsupporting
confidence: 96%
“…Several recent studies have described BS patients with no SCN5A mutations (Smits et al, 2002;Takahata et al, 2003;Shin et al, 2004). These results are consistent with our findings, which provide support for the possibility of genetic heterogeneity in BS (Priori et al, 2000).…”
Section: Discussionsupporting
confidence: 96%
“…In our patients with AVB, there were 7 sites of nucleotide change from exon 2 to exon 28 of the SCN5A gene. Among of them, 2 sites (G87A-A29A, IVS9-3C > A) were reported as genetic variations in a Western study [7], and T5457C-D1819D has already been reported as a variation or polymorphism without functional effects on the channel in Asian studies [7, 15, 16]. A1673G-H558R is located in the Na + channel I, II interdomain linker, and previous functional studies have shown that the H558R-encoding minor allele can alter the phenotype of true disease-causing SCN5A mutations [17].…”
Section: Discussionmentioning
confidence: 99%
“…These sodium channelopathies play a critical role in the pathogenesis of Brugada syndrome, 4 idiopathic ventricular fibrillation, 5 sudden infant death syndrome, 6 cardiac conduction defects, 7 congenital sick sinus syndrome, 8 atrial fibrillation 9 and overlapping syndrome. 10 Moreover, such genetic variations seem to modify responses to antiarrhythmic drug therapies, and to certain extent, to sensitize patients to the pro-arrhythmic effects of Na + channelblocking anti-arrhythmic agents.…”
Section: Discussionmentioning
confidence: 99%